Reckoning Informal Politics: Expands the Logic of Survival and Failure of Regional Heads - Sobari, Wawan (Jurnal Politik Indonesia: Indonesian Political Science Review, 2018)
The qualitative research addresses the political logic of why and how the incumbents succeed and fail in direct election for regional heads (pilkada) in emerging democratic Indonesia. De Mesquita et al. (2003) believe that, to survive in office, a leader needs to offer a benefit at least equal to the greatest possible benefit offered by a potential challenger. Particular to the pilkada cases in Indonesia, Erb and Sulistiyanto (2009) elaborate several factors connected to “reward and punishment” logic that may lead to the incumbents’ survival and failure in re-election bids. This study expands the logic by revealing that populism, rivalry, and tangibility are the core strategies for the successful incumbents in retaining their offices in four rural and urban regions in East Java. Particularly, the survival of an incumbent hinges on his capacity to manage rivalry risks, namely the capability to manage support and opposition both from formal and informal actors through fair or unfair means. These strategies, then, foster the success of patronage-based winning tactics to retain public office in the pilkada. To better assessment, it calls for the importance of democratic accountability as a complementary perspective (to consolidology) in measuring the progress of democracy in the country.